A new adaptive cascaded stochastic resonance method for impact features extraction in gear fault diagnosis - Li, Jimeng; Zhang, Yungang; Xie, Ping (Measurement : journal of the International Measurement Confederation, 2016)
•An adaptive SR enhancement method for weak impact signal detection is proposed.•The performance features of cascaded SR for weak signal detection are analyzed.•New measurement indexes are proposed to further improve the performance of SR.•The superiority of the proposed method is verified by experiments and application. Gearboxes are widely used in engineering machinery, but tough operation environments often make them subject to failure. And the emergence of periodic impact components is generally associated with gear failure in vibration analysis. However, effective extraction of weak impact features submerged in strong noise has remained a major challenge. Therefore, the paper presents a new adaptive cascaded stochastic resonance (SR) method for impact features extraction in gear fault diagnosis. Through the multi-filtered procession of cascaded SR, the weak impact features can be further enhanced to be more evident in the time domain. By analyzing the characteristics of non-dimensional index for impact signal detection, new measurement indexes are constructed, and can further promote the extraction capability of SR for impact features by combining the data segmentation algorithm via sliding window. Simulation and application have confirmed the effectiveness and superiority of the proposed method in gear fault diagnosis.